Cluster sets lead to better performance maintenance and minimize training-induced fatigue than traditional sets - Páez-Maldonado, José Antonio; Cornejo-Daza, Pedro Jesús; Sánchez-Valdepeñas, Juan; Sánchez-Moreno, Miguel; Piqueras-Sanchiz, Francisco; Ortega-Becerra, Manuel; Pareja-Blanco, Fernando (Frontiers in Sports and Active Living, 2024)
The aim of this study was to examine the acute effects on mechanical, neuromuscular, metabolic, and muscle contractile responses to different set configurations in full-squat (SQ). Twenty-two men performed three SQ sessions that consisted of 3 sets of 12 repetitions with 60% 1RM with 4 minutes inter-set rests: a) traditional set (TS): no rest within the set; b) cluster-6 (CS6): a 30 seconds intraset rest after the 6th repetition of each set; and c) cluster-2 (CS2): a 30 seconds intraset rest every 2 repetitions. Mechanical (i.e., force, velocity, and power) and electromyography (EMG) values were recorded for every repetition. A battery of tests was performed: a) tensiomyography (TMG), b) blood lactate c), countermovement jump (CMJ), d) maximal isometric SQ, and e) performance with the load that resulted in a velocity of 1 m·s−1 at baseline (V1-load). Repeated measured ANOVA analyses were used to compare the 3 protocols. As the number of intraset rests increased (TS